A Jordan Higher Reverse Left (resp. right) Centralizer on Prime ï‡-Rings - Jarullah, Fawaz Ra’ad; Salah Mehdi Salih (Iraqi Journal of Science, 2020)
In this paper, we introduce the concepts of higher reverse left (resp.right) centralizer, Jordan higher reverse left (resp. right) centralizer, and Jordan triple higher reverse left (resp. right) centralizer of G-rings. We prove that every Jordan higher reverse left (resp. right) centralizer of a 2-torsion free prime G-ring M is a higher reverse left (resp. right) centralizer of M.